Pengaruh Tingkat Pengetahuan dan Partisipasi Masyarakat dalam Pengelolaan Dana Desa terhadap pembangunan Desa Balunijuk Kecamatan Merawang Kabupaten Bangka: Studi kasus Desa Balunijuk Kecamatan Merawang Kabupaten Bangka - Roswita, Dina; Novriyanti, Irma (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
The level of knowledge and community participation is one of the important factors that influence the success of a village fund management program for the development of rural communities. This study aims to (1) determine the extent to which the level of knowledge of the Balunijuk village community regarding village fund management (2) analyzes the level of community participation in the development of Balunijuk village. This research was conducted on March 26, 2019. The method used is a qualitative method. Community participation is needed to realize village development in accordance with the needs of the village itself. Community participation not only involves the community in the implementation of village fund development in each development program, but the community is also involved in decision making and identifying problems that exist in the community. Without community participation every development activity will fail. Likewise, in relation to community participation in the use and management of village funds, this involvement is important so that the use and management can be more targeted and the benefits will be more relevant to the real interests of the community. But what happened in Balunijuk Village, Merawang Sub-District, Bangka Regency in terms of the use and management of village funds was still minimal due to community involvement or participation. This has an effect on community support for various programs that will be carried out using village funds. There are several factors that influence the level of community participation in village fund management, such as the lack of socialization from the village government regarding village fund programs, so that people do not understand the village fund program, which makes the community less participating. Besides that the education factor of the Balunijuk Village community is still lacking, so that the community is difficult to understand all the activities carried out by other people in the community.